2018
DOI: 10.1093/molbev/msy152
|View full text |Cite
|
Sign up to set email alerts
|

A Maximum-Likelihood Approach to Estimating the Insertion Frequencies of Transposable Elements from Population Sequencing Data

Abstract: Transposable elements (TEs) contribute to a large fraction of the expansion of many eukaryotic genomes due to the capability of TEs duplicating themselves through transposition. A first step to understanding the roles of TEs in a eukaryotic genome is to characterize the population-wide variation of TE insertions in the species. Here, we present a maximum-likelihood (ML) method for estimating allele frequencies and detecting selection on TE insertions in a diploid population, based on the genotypes at TE insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…The first papers on this topic supported rather the view that the selection is the most important factor, for example, in gathering TEs in regions of low or no recombination, [24,25] while more recent papers also demonstrated the role of TE targeting into specific regions (centromeres, heterochromatin, changed DNA conformation, higher transcription, etc.). [26,27] Nevertheless, the present study detecting selection on TE insertion confirms the general expectation that the majority of TE insertions are fixed [28] and thus, that TEs are more likely neutral and/or deleterious to the host. [29] TEs not only move from one site to another one in a genome and reshape the primary genomic structure but they can also contribute to dynamic changes of 3D nuclear architecture as was recently exemplified by the separate clustering of L1 and Alu/B1 retrotransposons in human and mouse genomes.…”
Section: Mobile Genetic Elements: a Plethora Of Forms And Spreading M...supporting
confidence: 86%
See 1 more Smart Citation
“…The first papers on this topic supported rather the view that the selection is the most important factor, for example, in gathering TEs in regions of low or no recombination, [24,25] while more recent papers also demonstrated the role of TE targeting into specific regions (centromeres, heterochromatin, changed DNA conformation, higher transcription, etc.). [26,27] Nevertheless, the present study detecting selection on TE insertion confirms the general expectation that the majority of TE insertions are fixed [28] and thus, that TEs are more likely neutral and/or deleterious to the host. [29] TEs not only move from one site to another one in a genome and reshape the primary genomic structure but they can also contribute to dynamic changes of 3D nuclear architecture as was recently exemplified by the separate clustering of L1 and Alu/B1 retrotransposons in human and mouse genomes.…”
Section: Mobile Genetic Elements: a Plethora Of Forms And Spreading M...supporting
confidence: 86%
“…The first papers on this topic supported rather the view that the selection is the most important factor, for example, in gathering TEs in regions of low or no recombination, [ 24,25 ] while more recent papers also demonstrated the role of TE targeting into specific regions (centromeres, heterochromatin, changed DNA conformation, higher transcription, etc.). [ 26,27 ] Nevertheless, the present study detecting selection on TE insertion confirms the general expectation that the majority of TE insertions are fixed [ 28 ] and thus, that TEs are more likely neutral and/or deleterious to the host. [ 29 ]…”
Section: Mobile Genetic Elements: a Plethora Of Forms And Spreading M...supporting
confidence: 85%
“…However, recent studies have demonstrated that TE play important roles in driving the evolution of genomes [ 8 ]. Transposable elements can promote genetic diversity through insertion [ 9 ] and regulate other factors such as genome size expansion [ 10 ], 3D organization [ 11 ], chromatin modifications [ 12 ], gene regulatory networks [ 13 ], and DNA methylation [ 14 ]. Transposable elements can be considered as a source of raw material for primitive genomes, tools of genetic innovation, and ancestors of modern genes (e.g., ncRNA) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%